PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PRODUK FASHION KOTA SEMARANG - Widi Fitria Lusiani; Agus Hermani DS (Jurnal Ilmu Administrasi Bisnis, 2019)
This research was conducted departing from the problem of high levels of complaints and low consumer satisfaction in e-commerce Lazada. This study aims to determine how the influence given by service quality and product quality on consumer satisfaction. The type of research used is explanatory type, with a total sample of 100 respondents with the characteristics of having made a purchase of fashion products on e-commerce Lazada, aged a minimum of 17 years, living in the city of Semarang both temporarily and permanently. This study consists of 3 variables, 24 indicators with 3 hypotheses. Data analysis methods used were validity and reliability, correlation coefficient (R), regression tests, coefficient of determination (R2), significance of the t test and F test with the application of SPSS 21.0. The results of this study indicate that service quality variables have a positive effect on customer satisfaction with results Y = 14.449 + 0.263 X1 and product quality has a significant and positive effect on customer satisfaction with results Y = 6.725 + 0.831 X2. Two variables have been tested simultaneously or together show the results of Y = 5,054 + 0,84X1 + 0, 756X2. The amount of contribution owned by the product quality variable is greater than the magnitude of the influence contribution owned by the service quality, the coefficient of determination (R2) for the service quality variable is 11.4% and product quality is 30.3%. Suggestions submitted are companies must improve service quality and product quality so that customer satisfaction is high, such as the speed of customer response, ease in the process of returns, certainty in the refund process, ease of contacting sellers, conformity between products received and offered, product durability, conformity standards product, because the 7 indicators are considered bad by consumers.